Bauran Pemasaran Hyaluronic Acid untuk Pengobatan Penyakit Ulcerative colitis - Atika Rani; Sri Widyastuti; Wahono Sumaryono; Henky Lesmana (JRB-Jurnal Riset Bisnis, 2020)
Ulcerative colitis (UC) is a chronic inflammatory condition in the proximal colon which is generally characterized by abdominal pain, diarrhea, fever and weight loss. Oral medication is usually used in the long term about 6 months or even for life. Study results show that hyaluronic acid (HA) has an important role in colon inflammatory diseases. HA is given by enema form for 28 days of therapy. This study was conducted to determine the doctors interest in HA enema products as an alternative therapy for UC disease treatment. This study is a qualitative exploratory descriptive study by in depth interview to Consultant Internist Gastroenterohepatology (KGEH) and Internist Specialist who treat UC disease patients which focuses on marketing mix, specifically product, price and promotion. The results showed that HA enema products could be accepted as an alternative choice for treatment therapy in UC patients with low to moderate severity in adolescent patients to the elderly.